Development and examination of group intervention package for promoting parent-adolescent relationship - Fatemeh Hoseini; Bagher Sanaee Zaker; Reza Pourhossein; Adis Keraskian (مجله علوم روانشناختی, 2017)
The majority of group action plans for intervention for parent- adolescent relationships are affected by individuation theory. But attachment theorists believe that due to the role of parents as a safe haven, the need for intimacy in this period will increase, but transform. The main issue of the present study is the separation of childhood from adolescence and the serious attention to attachment during adolescence. Therefore, the present study aimed to develop and evaluate a group action plan to promote the relationship between parents and adolescents in the form of an experimental design. The statistical population consisted of the parents of adolescents in region No.6 of Tehran, among which a randomly selected school was selected and parents were asked to participate in the project. Finally, 18 subjects in the experimental group and 17 in the control group randomly fitted. At first, the 21-item Parent-Adolescent Relationship Scale (PARS) (Husseini, Sanaee, Pourhossein, Karaskian, 2016) was provided to both groups. The experimental group was then subjected to a group action program promoting the relationship between parents and adolescents as independent variable for 9 sessions of 1.5 hours. At the end, both groups were again evaluated in terms of the relationship between the parent and the adolescent. Finally, 25 subjects (13 controls and 14 controls) were entered. Independent and dependent t test showed that the main hypothesis of the research was that "the researcher-made group action plan to improve the parent-teen relationship" promoted the parent-adolescent relationship (p <0.01). As a result, according to a qualitative interview with parents and adolescents, the group action plan was able to perfectly enhance the parent-adolescent relationship.